2007
DOI: 10.1111/j.1365-2249.2007.03391.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and a complement gene polymorphism interact in promoting cardiovascular disease morbidity and mortality

Abstract: SummaryWe have demonstrated previously that carriers of a genotype called C4B*Q0 (silent allele of the C4B gene) have a substantially increased risk to suffer from myocardial infarction or stroke, and are selected out from the healthy elderly population. Because smoking carries a major risk for cardiovascular disease (CVD), it seemed worthwhile to study if these two factors interact. Study 1 involved 74 patients with angina pectoris (AP), 85 patients with recent acute myocardial infarction (AMI) and 112 surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
9
18
0
Order By: Relevance
“…This finding is most probable due to the so-called smoker's paradox (25): compared with persistent smoker patients with AMI, non-smokers are younger and have fewer underlying medical problems, therefore at univariate analysis they have an apparently lower risk of death which, however, turns to the opposite after adjustment to the confounding variables. Higher mortality rate of the smoking AMI patients with low C4B copy number is in line with our previous findings (15) indicating that smoking carriers of this genotype exhibit an increased susceptibility for coronary artery disease and AMI and they are selected out for the healthy elderly population.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This finding is most probable due to the so-called smoker's paradox (25): compared with persistent smoker patients with AMI, non-smokers are younger and have fewer underlying medical problems, therefore at univariate analysis they have an apparently lower risk of death which, however, turns to the opposite after adjustment to the confounding variables. Higher mortality rate of the smoking AMI patients with low C4B copy number is in line with our previous findings (15) indicating that smoking carriers of this genotype exhibit an increased susceptibility for coronary artery disease and AMI and they are selected out for the healthy elderly population.…”
Section: Discussionsupporting
confidence: 77%
“…Interaction between smoking habits and C4B gene copy number in prediction of short-term mortality Previously, we reported an interaction between smoking and the C4B*Q0 carrier state for determining risk of CAD and myocardial infarction (15). In addition, in the present study we observed that smoking is weakly associated with mortality (Table 2).…”
Section: Multiple Regression Analysissupporting
confidence: 59%
See 2 more Smart Citations
“…T HE risk of developing many chronic diseases such as cancer, cardiovascular diseases, autoimmune diseases, and mental disorders may involve interactions among a number of genetic, endogenous, and exogenous environmental factors (Shields and Harris 2000;Talmud and Stephens 2004;Caspi and Moffitt 2006;Ambrosone et al 2007;Arason et al 2007). The successful identification of critical gene-environment interactions (GEI) may provide the scientific basis for preventative public health measures to help individuals with particular genetic susceptibilities reduce their exposure to disease risk-increasing environmental variables.…”
mentioning
confidence: 99%